UJI AKTIVITAS EKSTRAK BUNGA PEPAYA JANTAN SEBAGAI ANTIDIARE TERHADAP ESCHERICHIA COLI - Fitriana yuliastuti Yuliastuti (Jurnal Jamu Kusuma, 2021)
The purpose of this study was to study the activity of male papaya flower extract (Carica Papaya L) which was made as an antidiarrheal in order to provide insight and use of male papaya flowers (Carica Papaya L) as a study that discusses male papaya flowers are only used as cooking. This plant has a composition of compounds that contain antibacterial. The research method used was experimental research. The steps that have been carried out are determining the male papaya flower plant, extraction using male papaya flower simplicia powder with 70% ethanol solvent by maceration which is then evaporated on water to get a thick extract. Then make a bacterial suspension by incubating for 1x24 hours at 37 ° C. The results obtained show that the average inhibition zone at a concentration of 40% produces an average diameter of 2.6 cm, at a concentration of 30% produces an average diameter of 2.07 cm, and at a concentration of 20% produces an average diameter of 2.03 cm. The best concentration than the other series at a concentration of 40%. Keywords: Escherichia Coli, Carica Papaya L, Male Papaya Flowers